Analysis of the Concept of Justice in Al-Qur’an Hadith (Study of the Interpretation of M. Quraish Shihabin QS. An-Nisa Verse 135 on Youtube) - Liddini, Laily; Ade Surya Wilia Prabandani; Wardatun Nadhiroh (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
Allah SWT, ordered humans to be fair, both to themselves and to others, this is as stated in the QS. An-Nisa verse 135. Justice is a very important aspect of human life, especially in the life of the nation and state, to avoid division and also to obtain prosperity and security. Therefore, humans must be enforcers of fair justice. Because it is not uncommon or perhaps often justice enforcers who cannot act fairly for some reason. For enforcers of justice, it is very important and even obliged to have a high nature of justice. In responding to these problems, the writing will describe Quraish Shihab's interpretation of justice that must be done by someone for his own benefit or for others, in this paper the verse that will be discussed is QS. An-Nisa verse 135. The source of the interpretation is from the explanation of his interpretation in the video that discusses the verse. What is discussed in the interpretation of the verse is the command of Allah SWT., to be someone who is just and is able to be a fair witness. This research is using descriptive analytical method, namely describing the meaning of justice in the verse according to Quraish Shihab and analyzing the advantages and disadvantages of his interpretation. From the problems mentioned above, the writer aims to reveal what is in his interpretation.